Empirical validation of the spatial-choice modelling approach to user simulation. (4th July 2019) - Kim, Tae Wan; Cha, Seung Hyun
ABSTRACT: This empirical study sought to validate the spatial-choice modelling approach to user simulation. This validation is challenging, because spatial-choice behaviour is difficult to observe in real-life settings. To overcome this challenge, the study assembled 1137 activity cases from time-use diaries kept by university students and then extracted 74 space-rejection cases (i.e. events when students were unable to take up a particular space-option and so moved to another one). We assessed the attributes of the space-options in the rejection cases by means of a site investigation, predicted space-use probabilities using spatial-choice models, and assessed forecasting accuracy by a Brier score. The spatial-choice models scored 0.35, demonstrating higher forecasting accuracy than two alternative methods, namely space-use analysis (0.50) and the closest distance method (0.84). This study contributes to user simulation by validating the accuracy of the spatial-choice models based on revealed spatial-choice data in real-life settings and comparing it with other methods.